Kinetics of the adsorption of bovine serum albumin contained in a model wine solution by non-swelling ion-exchange resins - Sarmento, M.R. (2011)
Adsorption of wine proteins is an essential step in the production of white and rosé wines. In order to develop environmentally friendly adsorption processes, non-swelling adsorbents are required. The performance of selected non-swelling ion-exchange resins (Macro-Prep™ 50S and Streamline® SP) was studied by describing the process kinetics of the adsorption of BSA in a model wine solution. The process was assumed to be diffusion controlled and a shrinking core model was applied. Experiments were performed in the 5–35°C temperature range and with different equilibrium partition coefficients. The results obtained with the shrinking core model were theoretically consistent and the apparent diffusivity values correlated very well with theoretically estimated effective diffusivities combined with a linear dependence of porosity with temperature. Separating the temperature effect on porosity, the apparent diffusivity followed an Arrhenius type dependency with temperature with 16.9 kJ/mole activation energy.